1990
DOI: 10.1111/j.1365-2141.1990.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic bone marrow transplantation for secondary leukaemia and myelodysplastic syndrome: a survey by the Leukaemia Working Party of the European Bone Marrow Transplantation Group (EBMTG)

Abstract: This retrospective survey of the EBMT Leukaemia Working Party describes 78 patients with myelodysplasia (MDS) or secondary acute myelogenous leukaemia (sAML) who received an allogeneic bone marrow transplant (BMT). The status of underlying disease at the time of transplantation was prognostic for the 2-year disease-free survival. Thirty-four patients received intensive chemotherapy prior to the conditioning for BMT. The 2-year disease-free survival was 60% for the 16 patients transplanted in complete remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(83 citation statements)
references
References 20 publications
5
71
0
3
Order By: Relevance
“…23,24 Prolonged disease-free survival can be expected in only about 20% of patients transplanted for sAML. 25 Anderson et al 26 also reported that the 5-year survival of secondary AML patients was 24.4% after stem cell transplantation. The number of patients who benefit from allogeneic BMT is larger for AML-TLD than sAML because of the better CR rate and the lower ages of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…23,24 Prolonged disease-free survival can be expected in only about 20% of patients transplanted for sAML. 25 Anderson et al 26 also reported that the 5-year survival of secondary AML patients was 24.4% after stem cell transplantation. The number of patients who benefit from allogeneic BMT is larger for AML-TLD than sAML because of the better CR rate and the lower ages of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…19,21,44 Others have shown fewer relapses among patients with longer disease duration before transplant. 24 In the present series, patients with RAEB-T had a statistically significant higher relapse rate compared to patients with RA/RARS.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The Chronic Leukemia Working Party of the EBMT has collected data on several hundreds of patients transplanted for myelodysplasia and the first analysis was reported in 1990. 5 Two-thirds of the patients with MDS who may benefit from allogeneic BMT lack a suitable family donor. Increasing size of the donor registries has made allogeneic BMT with an unrelated donor a realistic alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Actuarial diseasefree survival (DFS) ranges between 35 and 45% at 2 to 4 years after BMT. [4][5][6][7][8] About 30% of younger patients with MDS/sAML will have an HLA-identical sibling donor and about 5% a one HLA locus mismatched family donor. Increasing size of the voluntary unrelated donor registries facilitates the identification of matched unrelated donors for about 75% of patients.…”
mentioning
confidence: 99%